Death of kings eaudiobook - Cornwell, Bernard (The Warrior Chronicles, 2012)
The Wall Street Journal hails New York Times best-selling author Bernard Cornwell as "the most prolific and successful historical novelist in the world today." in Death of Kings, the sixth novel in the Saxon Tales series, Alfred the Great is on his deathbed and the fate of the Angles, Saxons, and Vikings teeters on a knife's edge. Everything hinges on the actions of a single warrior, who must first come to grips with the mission he has no choice but to undertake.